TINJAUAN YURIDIS MEMUTUSKAN HUBUNGAN KERJA TERHADAP PEKERJA KONTRAK YANG PUTUS HUBUNGAN KERJA DALAM MASA KONTRAK DALAM PUTUSAN PHI NOMOR 6/V2/PDF-SUS-PHI/2021/PN.PBR - Ompusunggu, Erik Samarao; Siswanto, Wahyudi (Fakultas Hukum Universitas Trisakti, 2023)
Labor or labor issues are a typical problem we hear about in developing countries, including Indonesia. Related to this, termination of employment (PHK) is one of them. As happened with the unilateral termination of employment carried out by companies in Indonesia. In this writing the author uses normative legal research methods. Primary legal materials were obtained from Law no. 13 of 2003 concerning employment and secondary legal materials obtained from a review of legal literature, especially employment, papers, the internet and others. The implementation of termination of employment relations carried out by the company must be in accordance with Law No. 13 of 2003 concerning employment which states that termination of employment relations is carried out in several processes, namely holding a deliberation between the employee and the company, if an agreement cannot be obtained then the last resort is through the court to decide. case. Likewise, employees who resign are regulated in accordance with company regulations and laws. As a company's responsibility towards workers who have been laid off, the law requires or obliges the company to provide severance pay, reward money and compensation money. And the regulations regarding severance pay, reward money and compensation money are regulated in article 156, article 160 to article 169 of Law no. 13 of 2003 concerning Employment